Enhancing Adolescent Girls’ Knowledge of Premenstrual Syndrome through Flipbook and Video-Based Health Education - Safira Astri Atika Zahrani; I Wayan Arsana Wiyasa; Dian Kusumaningtyas (Jurnal Kebidanan dan Kesehatan Tradisional, 2025)
Background: Premenstrual syndrome (PMS) is symptom occur in luteal phase. The manifestation of PMS varies in each individual, may affect the quality of life in physical and physiological. Knowledge about PMS possibly improved through health education especially in adolescent girls as high-risk group. Flipbook and video are the media usually used for education; both are digital innovations that potentially facilitate the provision of health education. Methods: This quasi-experimental study was conducted by pre-posttest design without control group. A total population of 254 adolescent girls were selected for random sampling, resulting in 80 participants divided into two groups. The data was taken before and after education by questionnaires, analyzed with Wilcoxon test, and compared with Mann-Whitney test. Results: The result indicated there were increase to high level knowledge in flipbook group (50%) with mean score 77.83 and video group (72,5%) with mean score 85.33. The p-value using Wilcoxon test was p=<0.001 (p<0.01) respectively for both flipbook and video group. Mann-Whitney test resulted in higher effectiveness of video p=0.003 (p<0,05). Conclusion: There is increase in knowledge level after education both in flipbook and video groups. Meanwhile, video is highly suggested that the result shows higher effectiveness than flipbook.